Binuclear iron carbonyl complexes of thialene. Issue 86 (1st September 2016) - Jin, Rong; Chen, Xiaohong; Du, Quan; Feng, Hao; Xie, Yaoming; King, R. Bruce; Schaefer, Henry F.
Abstract : The low energy (thialene)Fe2 (CO)6 structure has an η 4, η 4 -thialene ligand bonded to two Fe(CO)3 units. The low-energy (thialene)Fe2 (CO)5 structure has an η 5, η 3 thialene ligand bonded to an Fe2 (CO)5 unit. Sulfur is not involved in ligand-metal bonding. Abstract : Thialene (C8 H6 S) is an isomer of benzothiophene and related to azulene by replacement of a CC unit in the seven-membered ring by a sulfur atom. The geometries of binuclear iron carbonyl complexes of thialene (C8 H6 S)Fe2 (CO) n ( n = 6, 5, 4) have been investigated using density functional theory for comparison with the corresponding azulene derivatives. The lowest energy (thialene)Fe2 (CO)6 structures have a bis(tetrahapto)-η 4, η 4 -thialene ligand bonded to two separate Fe(CO)3 units without involvement of the sulfur atom. This differs from the isomeric (benzothiophene)Fe2 (CO)6 structure known experimentally in which an iron atom has inserted into a carbon–sulfur bond to give a ferrathianaphthalene system. The only low-energy (thialene)Fe2 (CO)5 structure has a pentahapto-trihapto-η 5, η 3 thialene ligand bonded to an Fe2 (CO)5 unit, again without involvement of the sulfur atom. This structure is related to the experimental structure of azulene diiron pentacarbonyl, (η 5, η 3 -C10 H8 )Fe2 (CO)5 by replacement of the uncomplexed CC double bond in the seven-membered ring with the sulfur atom in the thialene six-membered ring. The potential energy surface of the unsaturated (thialene)Fe2 (CO)4 is very complicated but does not include any low-energy structures with formal FeFe double bonds. Thermochemical considerations suggest (thialene)Fe2 (CO)5 as a realistic synthetic objective, which is potentially accessible from reactions of thialene with Fe2 (CO)9 or (benzalacetone)Fe(CO)3 under mild conditions.